Video in situ simulation for medical student education during the COVID-19 pandemic - Bilic, Monika; Nagji, Alim; Hanel, Erich (Canadian Medical Education Journal, 2021)
Implication statement The COVID-19 pandemic has limited in-person experiences for medical students, especially in situations involving aerosol-generating procedures. We designed a video in situ simulation to orient students to critical steps in COVID-19 intubation algorithms. Small groups of students were paired virtually with facilitators (faculty and residents) and watched a video of an in situ simulation of emergency staff performing a protected intubation, with discussion points appearing on screen at discrete times. The simple design drives engagement, discussion and allows for scheduling flexibility with no risk to the learners. It can be adapted to several different scenarios or levels of training.